Eksistensi Pendidikan Karakter di Pondok Modern Darussalam Gontor Putri I Selama Pandemi Covid-19 - Mohammad Muslih; Muthmainnah Choliq; Ida Susilowati; Moh. Rofiq (Universitas Darussalam Gontor, 2021)
The Covid-19 pandemic has hampered the process of character building and has an impact on the moral decadence of students in schools. The lack of monitoring of the competence of educators in the online system causes a decrease in the character of students. This is due to the lack of exemplary in thinking, ethics, speaking, and acting obtained by students. It is important to instill character education in students so that they have characters based on religious values such as in Islamic boarding schools. This research aims to examine the existence of Islamic boarding schools in implementing character education in the pandemic era with the object Pondok Modern Darussalam Gontor (PMDG) for Girls 1 Mantingan Ngawi, East Java. This research is a literature study with the type of research is qualitatively, while the method is descriptive analytic. The results show that PMDG for Girls 1 is able to show its existence in implementing character education even in the pandemic era. This can be seen from the effectiveness of the dormitory system that can support face-to-face learning as an effort to internalize character education in Islamic boarding schools. This can be achieved by applying the discipline health protocol in the Pesantren environment before starting face-to-face learning. In addition, it is also supported by various Pesantren disciplines such as prohibiting students from leaving campus except in very emergency conditions and accompanied by special officers.